Fecal microbiome of pigs fed diets differing in protein and amino acid content raised in thermoneutral or cyclical heat stress conditions - de Oliveira, Marllon José Karpeggiane; Yang, Qinnan; Brandão Melo, Antônio Diego; Marçal, Danilo Alves; Korth, Nate; Pavlovikj, Natasha; Benson, Andrew K.; Htoo, John Khun Kyaw; Brand, Henrique Gastmann; Hauschild, Luciano; Gomes-Neto, Joao Carlos (Frontiers in Microbiology, 2025)
The pig microbiome composition is affected by factors such as dietary changes, genetics, and diseases. Recent evidence suggests that housing temperature may also contribute to the variability in community structure and composition. Therefore, we investigated the interactive effects of different nutritional strategies and heat stress (HS) on the fecal microbiota composition, community structure, taxon distribution, and taxa correlation structure of pigs. Forty-eight (Landrace × Large White) finishing gilts with an average of 67.7 ± 6.2 kg of body weight (BW) were distributed in a 2 × 3 factorial arrangement: two temperatures [thermoneutral (TN, 22°C for 24 h) and cyclic heat stress (CHS, 12 h to 35°C and 12 h to 22°C)] and three diets varying in the dietary crude protein (CP) contents and amino acid (AA) levels [high CP (HP); low CP-free AA-supplemented diet (LPAA); low CP-free AA-supplemented diet and digestible Lys level (+20%), and Lys:AA ratios above recommendations (LPAA+)] originating six treatments (eight replicates of one pig). Pigs were fed ad libitum throughout the study. The 16S ribosomal RNA (rRNA)-based microbiome analysis was conducted in fecal samples collected on days 0 and 27 (endpoint). Overall, microbiome analysis suggested an increased richness in the fecal microbiome of pigs raised in TN conditions fed a diet supplemented with higher levels of AA (LPAA+). In addition, changes in the fecal microbiome composition indicated that Mogibacterium was significantly diminished in the feces of pigs fed the LPAA diet when compared to pigs fed the LPAA+, both in CHS conditions. Oscillospira was reduced in the feces of pigs fed a diet containing exclusively protein-bound as the source of AA, while the more the feed-grade AA was included in the remaining diets, the more the abundance of this taxon in fecal samples. Despite dietary alterations, Corynebacterium was enriched under CHS compared to TN, whereas the enrichment of Prevotella and Eubacterium hallii group was higher in the TN group. Outcomes of this study suggest that changes in fecal microbiota composition were mainly associated with temperature, pointing toward potential taxa that may contribute to physiological adaptation to heat stress.